Metabolic Alterations in Cancer Cells and the Emerging Role of Oncometabolites as Drivers of Neoplastic Change - Zhengqiu Zhou; Elochukwu Ibekwe; Yevgen Chornenkyy (Antioxidants, 2018)
The mitochondrion is an important organelle and provides energy for a plethora of intracellular reactions. Metabolic dysregulation has dire consequences for the cell, and alteration in metabolism has been identified in multiple disease states—cancer being one. Otto Warburg demonstrated that cancer cells, in the presence of oxygen, undergo glycolysis by reprogramming their metabolism—termed “aerobic glycolysis”. Alterations in metabolism enable cancer cells to gain a growth advantage by obtaining precursors for macromolecule biosynthesis, such as nucleic acids and lipids. To date, several molecules, termed “oncometabolites”, have been identified to be elevated in cancer cells and arise from mutations in nuclear encoded mitochondrial enzymes. Furthermore, there is evidence that oncometabolites can affect mitochondrial dynamics. It is believed that oncometabolites can assist in reprogramming enzymatic pathways and providing cancer cells with selective advantages. In this review, we will touch upon the effects of normal and aberrant mitochondrial metabolism in normal and cancer cells, the advantages of metabolic reprogramming, effects of oncometabolites on metabolism and mitochondrial dynamics and therapies aimed at targeting oncometabolites and metabolic aberrations.